1996
DOI: 10.1017/cbo9781139170697
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anthropology

Abstract: Teeth are one of the best sources of evidence for both identification and studies of demography, biological relationships and health in ancient human communities. This text introduces the complex biology of teeth and provides a practical guide to the: • excavation, cleaning, storage and recording of dental remains • identification of human teeth including those in a worn or fragmentary state • methods for studying variation in tooth morphology • study of microscopic internal and external structure of dental ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
942
3
217

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,147 publications
(1,182 citation statements)
references
References 0 publications
20
942
3
217
Order By: Relevance
“…The occlusal relationship between upper and lower tooth rows and crown morphology (whether worn or unworn) are the primary agents responsible for delimiting where wear facets can be produced (Every, 1972;Schneck, 1981, 1982;Kaidonis et al, 1993;Hillson, 2003;Kaidonis, 2008). Biomechanical constraints such as masticatory muscles, jaw geometry, tooth shape, and crown size may also affect the position of wear facets.…”
Section: Introductionmentioning
confidence: 99%
“…The occlusal relationship between upper and lower tooth rows and crown morphology (whether worn or unworn) are the primary agents responsible for delimiting where wear facets can be produced (Every, 1972;Schneck, 1981, 1982;Kaidonis et al, 1993;Hillson, 2003;Kaidonis, 2008). Biomechanical constraints such as masticatory muscles, jaw geometry, tooth shape, and crown size may also affect the position of wear facets.…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz and Dean (2005) hypothesized that the size difference could be the result of a greater amount of dentin tissue present in male teeth. But other studies found very little sexual dimorphism in tooth size (Garn et al, 1964;Hillson, 1996;Mizoguchi, 1988). Harris (2003) reported that sexual variance accounted only for 1.2% of the total variation among studied groups.…”
Section: Introductionmentioning
confidence: 93%
“…Considering the variety of approaches and diversity of methods used in dental research (Hillson, 1996), we have attempted to clarify the issue by making inter-and intragroup comparisons based on a single, standardized, and quantitative procedure for measuring tooth size and dentin exposure .…”
Section: Page 4 Of 30mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dentine incorporates higher levels of lead, and is likely to represent a longer period of exposure than enamel. 30,31 We decided to focus on dentine lead levels as a marker of long-term lead exposure in this study, although comparisons with pre and post-natal enamel lead levels are made where appropriate.…”
Section: Figure 1 Herementioning
confidence: 99%